2013
DOI: 10.3892/or.2013.2790
|View full text |Cite
|
Sign up to set email alerts
|

Overcoming paclitaxel resistance in uterine endometrial cancer using a COX-2 inhibitor

Abstract: Cyclooxygenase (COX)-2 inhibitors have been reported to potentially modulate the resistance of cancer cells to chemotherapeutic drugs by affecting multidrug resistance 1 (MDR1) expression. In the present study, we investigated the association between COX-2 and MDR1 expression in endometrial cancers and evaluated the effects of the COX-2 inhibitor, etodolac, in combination with paclitaxel on paclitaxel-resistant endometrial cancer cells. The relationship between COX-2 and MDR1 mRNA expression was examined by qu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 29 publications
1
8
0
Order By: Relevance
“…Cox-2 and PGE 2 are up-regulated in many cancer tissues and can be suppressed by Cox-2 inhibitors [37]. The present study found that expression of PGE 2 and Cox-2 were elevated simultaneously under hypoxia.…”
Section: Discussionsupporting
confidence: 50%
“…Cox-2 and PGE 2 are up-regulated in many cancer tissues and can be suppressed by Cox-2 inhibitors [37]. The present study found that expression of PGE 2 and Cox-2 were elevated simultaneously under hypoxia.…”
Section: Discussionsupporting
confidence: 50%
“…Overall there is a theme that inhibition of COX pathways leads to potentiation of chemotherapeutic treatment in multiple gynecological malignancies including ovarian (Li et al, 2012a;Li et al, 2013), uterine (Hasegawa et al, 2013;Reader et al, 2019) and vulvar (Kim et al, 2009a). Additional studies are warranted to explore the role of and the mechanism behind adding inhibition of prostanoid receptors to chemotherapy and other treatment modalities in order to conserve potential antineoplastic eicosanoid activities for development of novel treatments for gynecologic malignancies.…”
Section: Resultsmentioning
confidence: 99%
“…Dual inhibition of COX-2 and mTORC1 signaling markedly reduces endometrial cancer progression (Daikoku et al, 2014). Paclitaxel resistance may be associated with COX-2 and multidrug resistance 1 (MDR1) expression, an efflux pump that can transport a wide range of compounds including chemotherapy out of the cell, in endometrial cancer (Hasegawa et al, 2013). Co-administration of COX-2 inhibitor etodolac with paclitaxel leads to a decrease in MDR1 expression which may enhance accumulation of MDR1 substrates such as paclitaxel thus leading to an increase in paclitaxel sensitivity (Hasegawa et al, 2013).…”
Section: Cyclooxygenase In Uterine Cancermentioning
confidence: 99%
See 1 more Smart Citation
“…Cyclooxygenase-2 (COX-2) is a key regulator of inflammation-producing prostaglandins and thus could be involved in inflammation-associated cancer development (15). Increased COX-2 expression has been found in a number of apoptosis-resistant cancer cells (16); therefore, COX-2 may be a potential target in the reversal of this apoptosis resistance. The expression of COX-2 has been shown to be modulated by several mechanisms, including the action of miRNA (17).…”
Section: Enforced Expression Of Mir-101 Enhances Cisplatin Sensitivitmentioning
confidence: 99%